Pendekatan scientific berbantuan Geogebra untuk meningkatkan mathematical problem solving - Dedi Nurjamil; Dian Kurniawan (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
The study, entitled “Scientific Approach To Improve GeoGebra aided Mathematical Problem Solving”, held in Mathematics Education, the Faculty of Education, Siliwangi University Tasikmalaya in Subjects Calculus 1. This research was conducted in order to follow up the results of previous studies the researchers did in Mathematics Education courses on learning styles. Research conducted by the author on a scientific approach to learning Calculus 1using GeoGebra Software. This study uses Mix Method with the sample consists of two classes, one experimental class using GeoGebra aided scientific approach and experimental class 2 uses a scientific approach is not aided software GeoGebra , Instruments used Mathematical Problem Solving Problem Tests, Observation Sheet, and Software GeoGebra. Posttest results showed the increased of normalized gain experimental 1 class better than experiment 2 class. The results of this research is produce output in the form of used textbooks and published journals.